Direct Preparation of Nanocelluloses of Tunable Lengths from Native Wood Via Alkaline Periodate Oxidation. (7th May 2021) - Yang, Ting; Liu, Peiwen; Xu, Dan; Wang, Jiaxiu; Zhang, Kai
Abstract: Herein, cellulose nanofibers (PO‐CNFs) and cellulose nanocrystals (PO‐CNCs) are prepared directly from native softwood spruce and hardwood beech via the same alkaline periodate oxidation under equal conditions. PO‐CNFs and PO‐CNCs are obtained by simply regulating the reaction time between 2 and 7 d. Of particular note, the preparation of CNFs is achieved using the alkaline periodate oxidation. PO‐CNFs obtained from spruce and beech have average diameters of 7.2 ± 3.1 and 6.8 ± 3.0 nm as well as average lengths of 487.1 ± 69.0 and 452.1 ± 80.0 nm, respectively. The PO‐CNCs obtained from spruce and beech are 4.6 ± 2.0 and 4.8 ± 2.5 nm in diameter as well as 181.6 ± 49.4 and 168.4 ± 59.0 nm in length, respectively. These nanocelluloses contain carboxy groups that enable good colloidal stability of nanocelluloses in water. The nanocellulose content isolated from spruce and beech increase with the reaction time and reach 1.35 ± 0.20 and 1.24 ± 0.10 mmol g –1 after oxidation for 7 d, respectively. Both PO‐CNFs and PO‐CNCs can be used for the formation of highly transparent films with good mechanical properties. Abstract : The preparation of two kinds of nanocelluloses as both cellulose nanofibers and cellulose nanocrystals with tunable dimensions and distinct aspect ratios is achieved by using alkaline periodate oxidation on native hardwood and softwood by only varying the reaction time.